acute tansverse myelitis in children - Tavasoli, Azita; Tabrizi, Aidin (Iranian Journal of Child Neurology, 2018)
Acute transverse myelitis (ATM) is a rare inflammatory and demyelinating disorder of spinal cord with an immune – mediated basis (1). It is potentially a devastating disorder with variable outcomes that can present with subacute onset of motor, sensory and autonomic dysfunction.(2) TM can occur as an isolated condition, usually as a postinfectious disorder or may be the first presentation of relapsing acquired demyelinating syndromes (ADS) that include acute disseminated encephalomyelitis (ADEM), multiple sclerosis (MS), and neuromyelitis optica (NMO). ATM also, must be distinguished from compressive and noninflamatory myelopathies. Diagnostic evaluation, prognosis, recurrence risk, and treatment plans are different among these entities